The Effect of E-Learning to Improve Learning Achievement and Student Learning Motivation in Entrepreneurship Subjects at SMKN 1 Bintan Utara - Marta Dewi Putri S; Nuril Huda; Muhajir Muhajir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the influence of the use of information and communication technology (ICT)-based learning media, especially E-Learning, on student learning achievement and learning motivation in Entrepreneurship subjects at SMK Negeri 1 Bintan Utara. The study delves into the challenges that arise in the use of E-Learning, including the lack of direct interaction and supervision, which has an impact on student motivation. The study found that although E-Learning provides flexibility in learning, its effect on improving learning achievement and motivation is not significant. Challenges such as limited access to technology and the digital divide are also factors that affect student learning outcomes.